Synthesis of liquid based biofertilizer and its impact on growth parameters of abelmoschus esculentus L. (Bangladesh Journal of Botany, 2026)
Phosphate biofertilizers are one of the effective methods for the improvement of agriculture and food security in the developing countries. Thus, the main objective of the current research was the isolation, identification of phosphate solubilizing bacteria, optimization of culture conditions, formulation of the liquid biofertilizer, and evaluation of its impact on the growth of Abelmoschus esculentus L. Soil samples collected from Charsadda district of Pakistan have been studied. Bacillus subtilis was isolated and identified. The isolates displayed holozonal activity on Pikovskaya agar media. The most efficient of them was B. subtilis 2 (PSI 128.57%). Highest growth of B. subtilis was observed at 35°C and pH 7. Biofertilizer had a significant impact on Abelmoschus esculentus seed germination. The germination percentage in 30% biofertilizer showed the highest root length, shoot length, fresh and dry weight. Urea fertilizer was less effective than biofertilizer. Liquid biofertilizers containing higher concentrations of B. subtilis greatly improve plant growth and soil phosphate availability.Bangladesh J. Bot. 55(2): 335-339, 2026 (June)